Innovative and efficient water management practice through value system in pipeline - Ranade, Deepak Hari; Mujalde, Santosh; Swarup, Indu (Indian Farming, 2018)
By using the system (device), it is evident that the border irrigation is no more labour and time consuming work and can be operated by unskilled-labour with better and efficient irrigation. Further it is to inform that this innovative idea came only after the construction of water harvesting tank in the field through one ICAR-funded project by ORP team. It is important to mention here that water-harvesting tank not onlycollects the runoff water but also can be used as storage tank for collecting tube-well water for its timely and efficient use. The increased water availability not only increases the crop productivity and farm income but it also gives confidence in the farmer to allow him to do experiments on various aspects of crop and water management.